Quitosana e óleos essenciais no controle de antracnose e na qualidade pós-colheita de abacates - Marques, Kelly Magalhães [UNESP] (2015)
This study aimed at evaluating alternative natural products, such as chitosan and essential oils, to control anthracnose in postharvest of 'Breda' and 'Hass' avocados. Ten plant-extracted essential oils were assessed regarding their initial antifungal potential against Colletotrichum gloeosporioides in vitro. Thymus vulgaris, Lippia sidoides and Cymbopogon citratus were selected among the oils for their outstanding inhibitory effects. Four experiments were performed in an in vitro stage, in which concentrations of chitosan and oils were tested in six replicates for each treatment. Then, five experiments were set in an in vivo stage, where in 'Breda' and 'Hass' avocados were immersed in different chitosan concentrations for 1 minute, as well as 'Hass' avocados were dipped in three concentrations of each essential oil associated with commercial wax. After drying and covering, 'Breda' avocados were stored at 22± 2 °C under 65± 5% RH for 7 days; and 'Hass' fruit were kept at 12± 2 ° C and 80 ± 5% RH for 14 days, then for more 3 days at 22 ± 2 °C and 65± 5%. Data underwent F test for variance analysis and means were compared by Tukey test (P≤0.05). Chitosan from 1.0% inhibits C. gloeosporioides mycelial growth and spore germination. The use of 1.0% chitosan in 'Breda' variety and at 2.0% in 'Hass' fruit, is effective in reducing of symptoms and incidence of anthracnose in the fruit, and also maintenance of quality. The thymol (T. vulgaris) and rosemary pepper (L. sidoides) oils from 200 μL L-1, inhibit mycelial growth, while concentrations of 500 and 1000 μL L-1 of oils with carnauba wax are more effective in reducing of symptoms of anthracnose, and by maintaining fruit quality of 'Hass' avocados